Identification of Defect Levels in Copper Indium Diselenide (CuInSe2) Thin Films via Photoluminescence Studies. (6th August 2018) - Shrestha, Niraj; Sapkota, Dhurba R.; Subedi, Kamala K.; Pradhan, Puja; Koirala, Prakash; Phillips, Adam B.; Collins, Robert W.; Heben, Michael J.; Ellingson, Randy J.
Abstract : Photoluminescence (PL) spectroscopy has been used to study the defect levels in thin film copper indium diselenide (CuInSe2, CIS) which we are developing as the absorber layer for the bottom cell of a monolithically grown perovskite/CuInSe2 tandem solar cell. Temperature and laser power dependent PL measurements of thin film CIS for two different Cu/In ratios (0.66 and 0.80) have been performed. The CIS film with Cu/In = 0.80 shows a prominent donor-to-acceptor peak (DAP) involving a shallow acceptor of binding energy ∼22 meV, with phonon replica at ∼32 meV spacing. In contrast, PL measurement of CIS film for Cu/In = 0.66 taken at 20 K exhibited an asymmetric and broad PL spectrum with peaks at 0.845 eV and 0.787 eV. Laser intensity dependent PL revealed that the observed peaks 0.845 eV and 0.787 eV shift towards higher energy (aka j-shift) at ∼11.7 meV/decade and ∼ 8 meV/decade with increase in laser intensity respectively. The asymmetric and broad spectrum together with large j-shift suggests that the observed peaks at 0.845 eV and 0.787 eV were related to band-to-tail (BT) and band-to-impurity (BI) transition, respectively. Such a band-tail-related transition originates from the potential fluctuation of defect states at low temperature. The appearance of band related transition in CIS film with Cu/In = 0.66 is the indicator of the presence of large number of charged defect states.